Thermal and economic evaluation of replacing pulverized coal with torrefied biomass in a small industrial burner in Thailand using computational fluid dynamics - Rachapat Chaiyo; Jakrapop Wongwiwat; Yanin Sukjai (Cleaner Engineering and Technology)
In response to the global warming crisis, the use of carbon-neutral biomass as a substitute for coal has gained significant attention due to its comparable combustion properties. This approach allows for minimal modifications to existing fuel systems. However, biomass has limitations, including its fibrous structure, which complicates grinding, and high moisture content, leading to lower power density and increased soot emissions. To overcome these challenges, torrefaction, a process involving the heating of raw biomass to around 200–300 °C, has emerged as a promising solution. This method improves the fuel's quality, reducing its moisture content and enhancing grindability, though it requires heat energy and raw material compensation for mass loss. This study employs computational fluid dynamics (CFD) modeling using ANSYS Fluent to analyze the combustion behavior of torrefied biomass produced under varying severity conditions. The results indicate that intensifying the torrefaction process increases combustion temperatures due to the fuel's higher calorific value and reduced moisture. Additionally, improved grinding capabilities reduce particle size, further enhancing combustion. Compared to conventional biomass, torrefied biomass shows a 28% increase in heat energy, rising from 220 to 279 kW, surpassing coal's 273 kW. Carbon monoxide emissions are significantly reduced by 93%, from 1044–72 kg/MWh, while coal emissions are 20 kg/MWh. However, nitrogen oxide emissions increased by 217%, from 0.17 to 0.54 kg/MWh, though still lower than coal's 0.72 kg/MWh. A cost analysis reveals that torrefaction conditions yielding a solid yield of 0.7 offers the lowest energy cost, approximately 114 Baht/GJ, a 14% reduction compared to conventional biomass and 37% lower than coal.